Nanomaterial-based wearable pressure sensors: A minireview. Issue 4 (3rd July 2020) - Liu, Runzhong; Xu, Ke; Zhang, Yu
Abstract: Wearable pressure sensors have great potential for applications in electronic skin, patient rehabilitation, and touch interfaces. In this paper, state-of-the-art achievements on typical low-dimensional nanostructured wearable pressure sensors and hybrid wearable pressure sensors are reviewed. In the two-dimensional-nanostructure section, two-dimensional transition metal carbides (MXenes) have a large specific area and excellent hydrophilicity, which ensures high sensitivity for pressure detection. Graphene can also represent two-dimensional nanostructured sensing materials due to its excellent transparency and carrier mobility. In the one-dimensional-nanostructure discussion, carbon nanotubes are promising one-dimensional nanostructure sensing materials due to their good mechanical and electronic properties. Silver nanowires have shown potential in the application of conductive fillers due to their excellent electrical properties and flexibility. In the zero-dimensional nanoparticle section, the metal oxide nanoparticles have been shown to be integrated with flexible substrates for sensors due to their large-area electronic uniformity. In the hybrid discussion, the use of electrical and chemical doping is reviewed to combine different nanomaterials to realize sensors with high performance. In each section, the present situation and major challenges are characterized. Next, the evolutions of the methods to overcome these challenges and most significant breakthroughs are demonstrated. In conclusion, future directions that may improve the performance of wearable pressure sensors are summarized.